The Effect of Antigibberellin Cultar , Ethaphon and Gbberellin on Surface Growth of Rhizoctonia so/ani and Fusarium oxysporum - AI-Qaisi, W.A; Janabi, S.J (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The     experiment     was     conducted    to     study     the     effect     ofantigibberellin   Cultar   ,  Ethephon   and  GA3   at  concentration   of (5,15,25 ppm) on surface growth of Rhizoctiona  solani and Fusraium oxysporum  . The results indicated that Cultar (15 , 25 ppm) decreased the      surface   growth   of     both   fungi   .  Ethephon   of   the   same concentration  significantly  reduced  the  growth  of  Fusarium oxysporum  .  The  number  of  sclerotia  of   Rhizoctiona    solani  was reduced by Cultar and GA3 at (15 ,25 ppm).